Assessment of Cochlear Implant Revision Surgeries in a Cohort of 802 Patients. Issue 4 (April 2019) - Karamert, Recep; Düzlü, Mehmet; Tutar, Hakan; Eravcı, Fakih Cihat; Türkcan, Alper Kutalmış; Zorlu, Mehmet Ekrem; Uğur, Mehmet Birol; Cebeci, Süleyman; Bezgin, Selin Üstün; Cevizci, Raşit; Bayazıt, Yıldırım Ahmet
Abstract : Objective: To assess the etiology, demographics, rates and outcomes of revision surgeries, and device survival rates after cochlear implantation. Study Design: Retrospective case review. Setting: Tertiary Otology & Neurotology center. Patients: Cochlear implantees who received revision surgeries after implantation Interventions: Any surgical intervention, performed due to device failure or the major complications of cochlear implantation. Main Outcome Measure: Medical records of the patients who received cochlear implants (CIs) between July 2002 and March 2018 were reviewed retrospectively regarding postoperative complications. Demographic data, device survival rates, and causes of revisions were recorded. Results: Totally, 924 implantations were performed in 802 patients. Eighty one (8.7%) of them underwent 102 revision surgeries. The most common causes of revision surgeries were device failures and flap related problems which were seen in 28 and 18 patients, respectively. Overall CI survival rate was 91.9% in a 10 years period, which remained almost stable after 10 years. Although age was not found to be related with device failure ( p  = 0.693), device loss rates were significantly higher in adult implantees than children ( p  = 0.006). Conclusion: Device failure seems the most common cause of revision. The revision surgeries are usually safe and help to resolve the problem although flap problems are the most difficult to treat and may necessitate multiple revision surgeries. The device failure rate may reach to a plateau after 6 years. Overall CI survival rate exceeds 90% in 10 years period, and then remains stable.